2021
DOI: 10.1016/j.phro.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implementation of artificial intelligence-driven cone-beam computed tomography-guided online adaptive radiotherapy in the pelvic region

Abstract: Background and purpose Studies have demonstrated the potential of online adaptive radiotherapy (oART). However, routine use has been limited due to resource demanding solutions. This study reports on experiences with oART in the pelvic region using a novel cone-beam computed tomography (CBCT)-based, artificial intelligence (AI)-driven solution. Material and methods Automated pre-treatment planning for thirty-nine pelvic cases (bladder, rectum, anal, and prostate), and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
154
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(163 citation statements)
references
References 29 publications
8
154
1
Order By: Relevance
“…Consequently, deliverables with artificial intelligence will be needed for accuracy in "real world [18]". Currently, auto-segmentation including a CNN method was implemented in some commercial treatment planning support systems [19][20][21][22][23][24]. DLCExpert ™ (Mirada Medical Ltd., UK), Ethos therapy system (Varian Medical Systems, Palo Alto, CA), and Limbus Contour (Limbus AI Inc., Regina, Canada) have the function of auto-segmentation using modified U-nets such as semantic segmentation [25] and BibNet [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, deliverables with artificial intelligence will be needed for accuracy in "real world [18]". Currently, auto-segmentation including a CNN method was implemented in some commercial treatment planning support systems [19][20][21][22][23][24]. DLCExpert ™ (Mirada Medical Ltd., UK), Ethos therapy system (Varian Medical Systems, Palo Alto, CA), and Limbus Contour (Limbus AI Inc., Regina, Canada) have the function of auto-segmentation using modified U-nets such as semantic segmentation [25] and BibNet [27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, auto-segmentation has great real-world clinical potential with the possibility of reducing time consumption [18]. Despite the number of published studies in this area, it is difficult to generalize these outcomes because it can only be used with dedicated treatment planning support systems [19][20][21][22][23][24][25]. Therefore, in this study, we develop and evaluate the accuracy of a software that can be used on the commercial radiation treatment planning system (RTPS).…”
Section: Introductionmentioning
confidence: 99%
“…(For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.) radiotherapy for esophageal cancer patients at dedicated X-ray based systems [25,26]. Previous studies on radiation-induced toxicity after chemoradiation for esophageal cancer showed multiple correlations between an increase in lung and heart dose and pulmonary and cardiac complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple online adaptive treatment platforms have been released by various vendors which allow for online replanning and thereby potentially by-passing all interfractional anatomy geometry variations. These platforms could either be based on X-ray imaging [25,26] or MR imaging [27][28][29] and could have onboard imaging capabilities that allow for online intrafraction monitioring to allow gating [30,31] and tracking [32] to mitigate effects from intrafraction motion.…”
mentioning
confidence: 99%
“…Reasonable adaptive treatment time has been reported for the Varian Ethos platform, which allows potential high patient throughput with ART. 16 One concern over CTgART is the lowimaging quality for online delineation and the lack of soft-tissue contrast for target visualization. Both FBCT and CBCT on the current ART platforms provide comparable image quality to the planning CT, which is already sufficient for many disease sites (head and neck, thorax, pelvis, spine, et al).…”
Section: Bin Cai Phdmentioning
confidence: 99%